Fighting the Financial Crisis with Alternative Forms of Energy in the Household Economics - Kostas Kyritsis; Evangelos Chytis; Kostas Karamanis (Proceedings of the 4th International Conference Entrepreneurship in the Global Environment: New Challenges in the Post-Crisis Era, 13-14 October 2011, TEI of Epirus - Dept. of Accounting, 2011)
We analyze how to fight the financial crisis at the level of Household Economics, by adopting environmental friendly alternative forms of energy, that reduce the CO2 emissions and the cost of living. The value of such green solutions is multiple: at the level of a better and healthier quality of life, at the level of planetary global climate crisis, and at the level of Household Economics. We utilize a specially coded simulator to represent the randomness of the input solar radiation variance both seasonally and as 11 years solar sunspot cycle, so as to calculate the financial risk of the household income. We propose a new Bank's financial product that links the solar energy income with the house mortgage payments. The solar energy alone as investment is approximately a 57% rate of return on equities or 20% internal rate of return. If it is linked with purchasing of the house, it can buy at least 30% of the house.
Keywords: O130; G170; 330; Household economics; Simulation; Renewable energy